A Pilot Study on the Influence of Diaphragmatic Function on Iliopsoas Muscle Activity in Individuals with Chronic Ankle Instability - Takumi Jiroumaru; Shun Nomura; Yutaro Hyodo; Michio Wachi; Junko Ochi; Nobuko Shichiri; Takamitsu Fujikawa (Muscles, 2025)
This study examined the impact of different breath-holding conditions on iliopsoas and other hip flexor muscle activity in individuals with chronic ankle instability (CAI). It has been hypothesised that impaired diaphragmatic function influences iliopsoas activation, potentially contributing to motor control deficits in patients with CAI. Eleven adults with a history of chronic ankle sprain participated in this study. Maximal isometric hip flexion was assessed under three breath-holding conditions: end-expiration, end-inspiration, and the intermediate state. Surface electromyography was used to record the muscle activity of the iliopsoas, rectus femoris, sartorius, and tensor fasciae latae, while the peak hip flexion torque was measured using an isokinetic dynamometer. Under the end-inspiration condition, iliopsoas activity on the affected side was significantly lower than that on the control side (p < 0.05). However, no significant differences were observed between the affected and control sides in the activity of the other hip flexor muscles or the peak hip flexion torque across breath-holding conditions. This study highlights the association between reduced iliopsoas activity during end-inspiration and compromised diaphragmatic function in patients with CAI. Future research should explore dynamic movement tasks and larger sample sizes to elucidate neuromuscular mechanisms further and refine rehabilitation strategies.